Ghana : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report, 2007)
This Ex-Post Assessment of Longer-Term Program Engagement for Ghana explains its experience with particular attention to the IMF's role. Progress in structural reform was slow, but Ghana also avoided mistakes made by some countries that introduced reforms without enough public support. Ghana's success in its reforms is embedded in the strengthening of democratic institutions that allow for greater public ownership of the reforms. Continual structural reform is essential to ensure that macroeconomic stabilization is durable. Recent slippages underscore the need to further improve fiscal institutions to control expenditures.